SOCIALIZATION OF ISLAMIC FINANCIAL CONTRACTS AND PRODUCTS AS AN ENDEAVOR TO INCREASE FINANCIAL LITERACY IN RURAL AREA - Faricha Maf'ula; Fifi Hakimi; Elvina Assadam (As-Sidanah, 2023)
Islamic financial literacy must be carried out massively in various communities. Islamic financial literacy is critical to improving Indonesia's Islamic financial ecosystem and meeting Indonesia's target of becoming a global Islamic economic and financial center by 2024. Therefore, this community service activity aims to conduct socialization in Islamic financial contracts and products to increase Islamic financial literacy in Indonesia in the women's community 'Aisyiyah Ranting Soko, Glagah, Lamongan, East Java. This activity used a service-learning approach with a form of socialization. The results of the community service showed that: (1) The mechanism for this activity was planning, implementation, and evaluation, which the assisted subjects could distinguish between conventional and Islamic finance, the concept of usury, and the supervisory board of Islamic financial institutions; and (2) there was a significant difference in the assisted subjects before and after socialization.